(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2008)
The evocative scenery of the middle-2nd century B.C. Athenian acropolis, where the Gigantomachy of the so called “Lesser Attalid Dedication”, erected south of the Parthenon, was in direct visual contact with the same theme of the Parthenon eastern metopes - testifying the strong cultural bond between Pergamon and Athens -, gives rise to a typological study of Giant iconography in the sculptural and pictorial representations of greek art between the Parthenon and the Attalid Dedication. The analysis of each figure of the Giants, but not out of its own monumental and historical-artistic context, produces a typological classification which can enlighten the tradition, the movement and the persistence of the different iconographical types used during the long history of the Greek Gigantomachy, with the main aim to find out how much of that bond one can recognize through the iconographical analysis of the two monuments.